A comparative study on the cyclic plasticity and fatigue failure behavior of different subzones in CrNiMoV steel welded joint. (January 2019) - Guo, Su-Juan; Wang, Run-Zi; Chen, Haofeng; Xuan, Fu-Zhen
Highlights: Comparative study on cyclic softening evolutionary characters in different subzones. Comparison of fatigue strength of different subzones in CrNiMoV welded joint. Study the ratcheting behavior of welded joints under different stress ratios. Comparison of cyclic and fatigue features for joints under different control mode. Explanation of the failure location shifting behavior in the welded specimen. Abstract: The cyclic plasticity and the low cycle fatigue failure behavior of the weld metal (WM) and base metal (BM) of the CrNiMoV steel welded joint under the strain and stress-control modes were investigated respectively. Significant cyclic softening was observed for both the WM and BM under the low cycle fatigue tests with the two control modes. Besides, obvious ratcheting happened in the WM and BM under the stress-controlled cyclic loading conditions. It is shown that both the WM and BM exhibited lower fatigue strength at the stress control mode than that at the strain control mode due to the influence of tension-compression asymmetry. Meanwhile, the WM showed larger cyclic softening rate, lower ratchetting deformation and fatigue strength than the BM under the same loading levels. The failure location of the WM specimens shifted from BM region (nearby the heat affected zone) to the center of WM with the increasing of strain amplitude under the strain-controlled tests, which can be explained with the similar maximum equivalent plastic strain amplitude location shifting behavior observed from the corresponding finite element simulations. Graphicalabstract :